A description of the reproductive behaviour of the endangered Iberian cyprinid Chondrostoma lusitanicum Collares-Pereira 1980 in captivity - Carvalho, Vera Susana Dias (2012)
In this paper we describe, for the first time, the reproductive behaviour of the rare Iberian cyprinid fish Chondrostoma lusitanicum, endemic to Portugal. The species is an egg broadcaster releasing adhesive eggs. Spawning aggregations may involve large numbers of fish but within a group, short sequences of courtship and spawning typically involve one female and one or a few males. Males follow females touching them frequently and at spawning press the female body against the available objects. Males perform circles that may help to retain a female in a given area. A special behaviour is described for females with the likely function of attracting males and initiating courtship.